2011
DOI: 10.1111/j.1651-2227.2011.02235.x
|View full text |Cite
|
Sign up to set email alerts
|

48,XXYY, 48,XXXY and 49,XXXXY syndromes: not just variants of Klinefelter syndrome

Abstract: Sex chromosome tetrasomy and pentasomy conditions occur in 1:18 000–1:100 000 male births. While often compared with 47,XXY/Klinefelter syndrome because of shared features including tall stature and hypergonadotropic hypogonadism, 48,XXYY, 48,XXXY and 49,XXXXY syndromes are associated with additional physical findings, congenital malformations, medical problems and psychological features. While the spectrum of cognitive abilities extends much higher than originally described, developmental delays, cognitive im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
151
0
13

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(172 citation statements)
references
References 59 publications
(120 reference statements)
8
151
0
13
Order By: Relevance
“…The above-mentioned dysmorphic findings and truncal obesity were present also in our patient. Submucosal or hidden cleft palate have been reported previously, whereas incomplete cleft lip found in our patient has not been identified in previous cases (6). Toe deformities found in our patient are another dysmorphic finding which has not been identified before.…”
Section: Discussionmentioning
confidence: 32%
See 1 more Smart Citation
“…The above-mentioned dysmorphic findings and truncal obesity were present also in our patient. Submucosal or hidden cleft palate have been reported previously, whereas incomplete cleft lip found in our patient has not been identified in previous cases (6). Toe deformities found in our patient are another dysmorphic finding which has not been identified before.…”
Section: Discussionmentioning
confidence: 32%
“…Tartaglia et al (5) reported that increase in height accelerated especially from the period of puberty. While long height has also been reported in 48,XXXY syndrome, individuals with 48 XXXXY syndrome are mostly short (6). Although our patient was in the prepubertal period, his height was in the 90th percentile.…”
Section: Discussionmentioning
confidence: 82%
“…48, XXYY syndrome is extremely rare with an incidence of 1:18000 -1: 100,000 males [4,[9][10][11]. 48, XXYY syndrome is usually caused by double non-disjunction occurring at both the first and second meiotic division during spermatogenesis and fusion of the resulting 25, XYY spermatozoon with a 23, X ovum, or nondisjunction at the second meiotic division in both parents resulting in the fusion between a 24, XX ovum and a 24, YY sperm [2].…”
Section: Discussionmentioning
confidence: 99%
“…With each additional X chromosome there is progressive divergence from the normal with increased frequency of phenotypic, endocrine and structural abnormalities [3]. Poly X-syndrome, often described in literature as a variant of KS, is much rarely reported with a prevalence of 1:18,000-1:100,000 male births and has more pronounced congenital malformations and associated medical comorbidities [4]. We describe a case of a patient who had a formal diagnosis of classic KS from a very young age of 14, presented with not only behavioral and cognitive impairment but also with a wide spectrum of medical complications and further identified on reassessment as XXYY genotype.…”
Section: Introductionmentioning
confidence: 99%
“…Physical characteristics include dysmorphic facial features, elbow abnormalities and poor muscle development. Common medical problems are asthma, peripheral vascular disease, diabetes and intention tremors [3]. The presence of an extra Y chromosome affects neurodevelopment, resulting in developmental delays, learning disabilities, intellectual disabilities, and a spectrum of psychological disorders which differentiates it from Klinefelter syndrome (47, XXY), in which the intellect usually falls in the average range (IQ = 80-120) [4,5].…”
Section: Introductionmentioning
confidence: 99%